Performance of single and mixed rhizobial inoculants on nodulation, dry matter and seed yield of lentil (Lens culinaris) (Bangladesh Journal of Agricultural Research, 2014)
Field experiments were carried out at Regional Agricultural Research Station (RARS), Ishurdi, Pabna during the rabi season of 2005-06 and 2006-07 to find out the effectiveness of Rhizobium strains for achieving higher yield of lentil, the variety BARI Masur4. There were six treatments that were Rhizobium strains- BARI RLc-104, BARI RLc-105, BARI RLc-106, BARI RLc107, mixed culture of the four strains, and control (no Rhizobium). The experiment was designed in randomized complete block having 4 replications of each treatment.The rhizobial inocula were peat based and used @ 1.5 kg/ha. A basal dose of P @ 22 kg/ha, K @ 42 kg/ha, S @ 20 kg/ha, and @ 5 kg Zn/ha was used for all treatments. The highest nodule number (11.7/plant in 2006 and 10.3/plant in 2007) and dry nodule weight (10.53 mg/plant in 2006 and 9.58 mg/plant in 2007) were found with mixed culture. Mixed culture produced the highest seed yield in 2006 (1.36 t/ha, 37.4% higher over uninoculated control) and in 2007, BARI RLc-104 recorded the highest seed yield (1.23 t/ha, 60.3% higher over uninoculated control). However, all the strains including mixed culture had similar seed yields over the years. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20147 Bangladesh J. Agril. Res. 39(1): 105-112, March 2014